ANALYSIS OF FACTORS AFFECTING EFFECTIVE TAX RATES OF COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2009-2018 - Dailimi, Lili Fajri; Setyowati, Milla Sepliana (Jurnal Administrasi Publik : Public Administration Journal, 2020)
Stock Exchange This study aims to determine whether company size, profitability, leverage, the proportion of independent commissioners and government ownership have an influence on the company's effective tax rates both jointly and partially. This was tested on companies listed on the Indonesia Stock Exchange by means of statistical testing through a panel data regression model that was processed using the STATA 12.0 application. Secondary data used in this research were collected using content analysis techniques. The research sample was determined by a purposive sampling technique on companies in the sectoral index consisting of 10 sectors listed on the Indonesia Stock Exchange with the study period 2009-2018. The independent variables used in this study are company size, profitability, leverage, the proportion of independent commissioners and government ownership, while the dependent variable is the company's effective tax rate. The results showed that the size of the company, the level of profitability of return on assets and corporate governance that are proxied by the proportion of independent directors have a significant effect on effective tax rates, although with different correlations. Where firm size is negatively correlated, while the level of profitability and corporate governance has a positive effect on effective tax rates. Meanwhile, leverage and government ownership variables tend not to have a significant effect on effective tax rates.